Fluxional Bonds in Planar B19−, Tubular Ta@B20−, and Cage‐Like B39 - Yan, Miao; Li, Hai‐Ru; Zhao, Xiao‐Yun; Lu, Xiao‐Qin; Mu, Yue‐Wen; Lu, Hai‐Gang; Li, Si‐Dian (Journal of computational chemistry, 2019)
Based on detailed bonding analyses on the fluxional behaviors of planar B19−, tubular Ta@B20−, and cage‐like B39−, we propose the concept of fluxional bonds in boron nanoclusters as an extension of the classical localized bonds and delocalized bonds in chemistry. © 2018 Wiley Periodicals, Inc. Detailed bonding analyses on fluxional boron nanoclusters suggest the existence of fluxional bonds in electron‐deficient systems with low energy barriers as an extension of the classical localized bonds and delocalized bonds in chemistry.